2006
DOI: 10.1152/japplphysiol.01072.2005
|View full text |Cite
|
Sign up to set email alerts
|

Reduced exercise-associated response of the GH-IGF-I axis and catecholamines in obese children and adolescents

Abstract: Obesity blunts catecholamine and growth hormone (GH) responses to exercise in adults, but the effect of obesity on these exercise-associated hormonal responses in children is unclear. Therefore, the aim of the present study was to asses the effect of childhood obesity on the counterregulatory hormonal response to acute exercise. Twenty-five obese children (Ob; body mass index > 95%), and 25 age, gender, and maturity-matched normal-weight controls (NW) participated in the study. Exercise consisted of ten 2-min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
41
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 51 publications
10
41
2
Order By: Relevance
“…The exercise-induced decrease in insulin in all groups was similar to observations during aerobic exercise [14, 23]; this finding highlights the role of exercise in insulin control [8, 10]. Previous investigations suggested a lower degree of insulin resistance in PWS when compared to nonsyndromic obesity [24, 25].…”
Section: Discussionsupporting
confidence: 82%
“…The exercise-induced decrease in insulin in all groups was similar to observations during aerobic exercise [14, 23]; this finding highlights the role of exercise in insulin control [8, 10]. Previous investigations suggested a lower degree of insulin resistance in PWS when compared to nonsyndromic obesity [24, 25].…”
Section: Discussionsupporting
confidence: 82%
“…As stated earlier, we previously demonstrated that the GH response to exercise is inhibited in obese children and adolescents [8]. This reduced exercise-induced GH response was suggested to be associated with a lower training effect, which may explain the limited success of weight reduction interventions in changing body composition and improving physical fitness in obese children and adolescents.…”
Section: Discussionmentioning
confidence: 75%
“…It is suggested that the effects of exercise training are related to the balance between the exercise-induced anabolic/catabolic and inflammatory response [7]. Interestingly, the exercise-associated increase in GH usually seen in normal-weight children is significantly attenuated in obese children and adolescents [8]. It was suggested that the reduced GH response to exercise leads to a lesser effect of training in obese children, and may explain the limited success of weight reduction interventions in changing body composition and improving physical fitness in obese children and adolescents [9].…”
Section: Introductionmentioning
confidence: 99%
“…In an 18-year follow-up study, a low epinephrine response to a mental challenge was a predictor for body mass gain in men [30]. Other experimental studies confirmed that obese subjects exhibit an inadequate sympatho-adrenal system response to different stimuli such as exercise [31], cold [32], and oral glucose load [33]. Similarly, obesity-prone rats are known to exhibit an inadequate sympatho-adrenal system response to hypoglycemia [34], overfeeding [35], and chronic stress [36].…”
Section: Discussionmentioning
confidence: 99%